2002
DOI: 10.1074/jbc.m200678200
|View full text |Cite
|
Sign up to set email alerts
|

Oxyresveratrol and Hydroxystilbene Compounds

Abstract: Tyrosinase is responsible for the molting process in insects, undesirable browning of fruits and vegetables, and coloring of skin, hair, and eyes in animals. To clarify the mechanism of the depigmenting property of hydroxystilbene compounds, inhibitory actions of oxyresveratrol and its analogs on tyrosinases from mushroom and murine melanoma B-16 have been elucidated in this study. Oxyresveratrol showed potent inhibitory effect with an IC 50 value of 1.2 M on mushroom tyrosinase activity, which was 32-fold str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(101 citation statements)
references
References 41 publications
3
94
1
3
Order By: Relevance
“…Remaining stilbenes which had resorcinol moiety (1-3) and/or destroyed catechol moiety (6)(7)(8) had lower ABTS radical scavenging activity than catecholic stilbenes (4 and 5) (Table 1). Fortunately, almost all synthetic stilbenes 1-8 showed (4) 4.1 ± 1.1 (4.8) 95.7 ± 1.4 8.6 trans -3',4'-Dihydroxy -3,5-dimethoxystilbene (5) 10.3 ± 0.7 (1.9) 40.6 ± 0.8 > 100 trans-4'-Hydroxy -3, 3',5-trimethoxystilbene (6) 17.4 ± 0.9 (1.1) 14.5 ± 2.5 > 100 trans-3'-Hydroxy -3, 4',5-trimethoxystilbene (7)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remaining stilbenes which had resorcinol moiety (1-3) and/or destroyed catechol moiety (6)(7)(8) had lower ABTS radical scavenging activity than catecholic stilbenes (4 and 5) (Table 1). Fortunately, almost all synthetic stilbenes 1-8 showed (4) 4.1 ± 1.1 (4.8) 95.7 ± 1.4 8.6 trans -3',4'-Dihydroxy -3,5-dimethoxystilbene (5) 10.3 ± 0.7 (1.9) 40.6 ± 0.8 > 100 trans-4'-Hydroxy -3, 3',5-trimethoxystilbene (6) 17.4 ± 0.9 (1.1) 14.5 ± 2.5 > 100 trans-3'-Hydroxy -3, 4',5-trimethoxystilbene (7)…”
Section: Resultsmentioning
confidence: 99%
“…5 This enzyme is responsible for browning of fruits and coloring of skin in animals including human being. 6 Inhibitors of tyrosinase is important molecular tools for food quality and skin whitening in human. The strong tyrosinase inhibitor, such as piceatannol, has potential applications as whitening agent in cosmetic preparations or anti-browning agent for food products.…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that oxyresveratrol inhibited tyrosinase activity more than resveratorol (3,4?,5-trihydroxystilbene). 13) We have also observed that resveratrol inhibited tyrosinase activity, but was less eŠective than gnetol (data not shown). Therefore, the number of hydroxy substituents seems to play an important role in the inhibitory potency of hydroxystilbene compounds for tyrosinase activity.…”
mentioning
confidence: 77%
“…Recently, Kim et al 13) have demonstrated that oxyresveratrol (2,3?,4,5?-tetrahydroxystilbene) from Morus alba Linne was a potent inhibitor of tyrosinase activity. Gnetol is chemically related to oxyresveratrol, which is a tetrahydroxystilbene.…”
mentioning
confidence: 99%
“…Proses pencoklatan menyebabkan terjadinya perubahan nutrisi dan organoleptik sehingga menyebabkan perubahan mutu yang tidak dikehendaki 28,29 . Banyak faktor yang dapat menyebabkan terjadinya proses pencoklatan antara lain kondisi penyimpanan, waktu penyimpanan serta terjadinya oksidasi senyawa fenolik menjadi quinon yang dikatalisis oleh polyphenol oxidase (PPO) 30 .…”
Section: Hasil Dan Pembahasan Parameter Mutu Fisik Indeks Browningunclassified